Upaya Meningkatkan Hasil Belajar Lari Jarak Menengah 800 Meter Melalui Penguatan Umpan Balik dan Pendekatan Saintifik pada Siswa Kelas VII SMP Negeri 2 Kutacane - Afrizal, Afrizal; Boihaqi, Boihaqi; br. Panggabean, Marsyah (Medan Resource Center, 2023)
The research findings indicate a significant positive impact on the learning process for the 800-meter middle distance run when employing a direct feedback reinforcement learning model and a scientific approach. The analysis reveals noteworthy improvements, with a 2.38% increase in the average student learning outcomes compared to the previous test. Furthermore, there was a substantial classical increase of 34.37%. Notably, the results of the second cycle demonstrate the attainment of the anticipated classical learning completeness criteria. This underscores the effectiveness of innovative and creative learning models in Physical Education, highlighting their essential role in accomplishing educational objectives. The study contributes valuable insights into pedagogical strategies that enhance student performance in sports education, providing a foundation for further research and educational practices.